Interaction of rat alveolar macrophages with dental composite dust. Issue 1 (December 2016) - Van Landuyt, K.; Cokic, S.; Asbach, C.; Hoet, P.; Godderis, L.; Reichl, F.; Van Meerbeek, B.; Vennemann, A.; Wiemann, M.
Abstract Background Dental composites have become the standard filling material to restore teeth, but during the placement of these restorations, high amounts of respirable composite dust (<5 μm) including many nano-sized particles may be released in the breathing zone of the patient and dental operator. Here we tested the respirable fraction of several composite particles for their cytotoxic effect using an alveolar macrophage model system. ​Methods Composite dust was generated following a clinical protocol, and the dust particles were collected under sterile circumstances. Dust was dispersed in fluid, and 5-μm-filtered to enrich the respirable fractions. Quartz DQ12 and corundum were used as positive and negative control, respectively. Four concentrations (22.5 μg/ml, 45 μg/ml, 90 μg/ml and 180 μg/ml) were applied to NR8383 alveolar macrophages. Light and electron microscopy were used for subcellular localization of particles. Culture supernatants were tested for release of lactate dehydrogenase, glucuronidase, TNF-α, and H2 O2 . Results Characterization of the suspended particles revealed numerous nano-sized particles but also many high volume particles, most of which could be removed by filtering. Even at the highest concentration (180 μg/ml), cells completely cleared settled particles from the bottom of the culture vessel. Accordingly, a mixture of nano- and micron-scaled particles was observed inside cells where they were confined to phagolysosomes. The filtered particle fractions elicited largely uniform dose-dependent responses, which were elevated compared to the control only at the highest concentration, which equaled a mean cellular dose of 120 pg/cell. A low inflammatory potential was identified due to dose-dependent release of H2 O2 and TNF-α. However, compared to the positive control, the released levels of H2 O2 and TNF-α were still moderate, but their release profiles depended on the type of composite. Conclusions Alveolar macrophages are able to phagocytize respirable composite dust particle inclusive nanoparticles. Since NR8383 cells tolerate a comparatively high cell burden (60 pg/cell) of each of the five materials with minimal signs of cytotoxicity or inflammation, the toxic potential of respirable composite dust seems to be low. These results are reassuring for dental personnel, but more research is needed to characterize the actual exposure and uptake especially of the pure nano fraction.